(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
Pausanias’s periegesis is the touchstone of humanism in the recovery of Greece. It had a definite impact on the perception of Greece in Western Europe during the Renaissance and the Enlightenment. Today all antiquity experts recognize the decisive contribution of Pausanias’s itinerary to the reconstruction and documentation of the monumental topography of ancient Greece. However, such an axiomatic position has caused many objections in earlier times, when many scholars doubted his sincerity (e.g. Wilamowitz), or his reliability. The excavations at the sanctuary of Delphi and accompanying research gave new life to many of the votives Pausanias saw and tend in many cases to justify the reliability of his text. At the same time, however, comparison of the periegetes words to the archaeological remains raised many problems, such as the identification of the offering by the citizens of Tegea, or the interminable discussion concerning whether the Treasury of the Athenians was built just before, or after the battle of Marathon. The unexpected identification of a series of sculptures with the statues from the two pediments of the 4th century Temple of Apollo in the recent years and the important reconstruction of their representations exactly as Pausanias described them, allows today the periegetes to have the final word over his older censors.